2010
DOI: 10.1021/jf1033202
|View full text |Cite
|
Sign up to set email alerts
|

A-Type Proanthocyanidins from Lychee Seeds and Their Antioxidant and Antiviral Activities

Abstract: Two new A-type trimeric proanthocyanidins with two doubly bonded interflavanoid linkages, litchitannin A1 [epicatechin-(2β→O→7,4β→6)-epicatechin-(2β→O→7,4β→8)-catechin] (1) and litchitannin A2 [epicatechin-(2β→O→7,4β→6)-epicatechin-(2β→O→7,4β→6)-epicatechin] (2), were isolated from lychee (Litchi chinensis Sonn. cv. Heiye) seeds together with aesculitannin A (3), epicatechin-(2β→O→7,4β→8)-epiafzelechin-(4α→8)-epicatechin (4), proanthocyanidin A1 (5), proanthocyanidin A2 (6), proanthocyanidin A6 (7), epicatechi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(68 citation statements)
references
References 25 publications
3
62
2
1
Order By: Relevance
“…To the best of our knowledge, this is the first report to show that LCSP can inhibit proliferation of CRC cells. Previous studies have revealed that Litchi seeds are mainly composed of lichitanin A and proanthocyanidin [13]. The major structure of lichitanin is catechin and epicatechin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report to show that LCSP can inhibit proliferation of CRC cells. Previous studies have revealed that Litchi seeds are mainly composed of lichitanin A and proanthocyanidin [13]. The major structure of lichitanin is catechin and epicatechin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Litchi pericarp is the edible part of the Litchi fruit, and overdosing may lead to some consumers' uncomfortable “heating” [12]. In recent reports, polyphenol compounds from Litchi seeds were identified and composed of a variety of proanthocyanidins and flavonoid glycoside [13, 14]. Some of these compounds appear to exhibit antineoplasm activities in lung cancer, cervical cancer and hepatocellular carcinoma cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…As a famous traditional Chinese medicine, lychee seed (Lizhi He in Chinese) has been recorded in the Compendium of Materia Medica ( Bencao Gangmu ) and exhibits many beneficial effects including anti-tumor [15], anti-oxidation [16], anti-virus [17,18], preventing liver injury [19], improving insulin resistance (IR) and sensitivity [20,21], and other pharmacological effects. Previous studies have shown that the chemical constituents of lychee seed are mainly saponins, organic acids, fatty acids, amino acids, sugars, and flavonoids [15].…”
Section: Introductionmentioning
confidence: 99%
“…The seeds also have the reputation of relieving neuralgic pain in China. In recent studies, a variety of proanthocyanidins, flavonoid glycosides and polysaccharides were identified from litchi seeds [79]. Some of these compounds appeared to exhibit anti-neoplastic activities in breast cancer, sarcoma, nasopharynx cancer, lung cancer, cervical cancer and hepatocellular carcinoma cell lines [7, 8, 10, 11].…”
Section: Introductionmentioning
confidence: 99%